Giving Space to the Tabooed Trauma: Sofia Taikon’s Testimony in Katitzi Z-1234 and Sofia Z-4515 - Hertrampf, Marina Ortrud M. (Porównania, 2023)
Repression and concealment of one of the worst traumatic experiences of the 20th century affects Europe’s largest minority in a massive way. In contrast to the Shoa, the Porajmos is little known to many people of both the majority and the minority. Often repressed as a taboo, breaking the silence about this trauma is of central relevance for the self-confidence of the Roma, especially those born afterwards. In fact, in the case of victims and their children and grandchildren, there is a tension between repression and concealment on the one hand and the need to overcome trauma on the other. Using the example of two educational works for young minority and majority readers in which the painful memories of Polish Romani Sofia Taikon, born Brzezinska, are fictionalised, the article illustrates how this tension is dealt with and how space is given to the long-tabooed trauma.